Job Satisfaction of Nurses from Clinical Practice in Jiroft University Hospitals - M Faramarzpour; F Borhani; P Bagheri (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Job satisfaction is the level of employees' feelings regarding their jobs in most the health care organizations nurses are the largest human resources and play a major role in the quality of services, thus their satisfaction and efficiency significantly affects the success of the organization. The current study conducted to determine the job satisfaction from clinical practice in nurses working in Jiroft university hospitals, Iran.  Material & Method: In this cross sectional study that was conducted in 2013, participants completed the standardized Luthans questionnaire with 41 questions about job satisfaction. Reliability and validity of this questionnaire were 84% and 94% respectively. SPSS software and descriptive statistic, t-test, ANOVA and Pearson correlation coefficients were used for data analysis. Results: The average of nurse's job satisfaction was 2/7 ±0/5 with a minimum of 1/1 and maximum of 4/8 .The highest job satisfaction was related to pediatric and neonatal wards (p> 0/05). The lowest level of job satisfaction was related to intensive care wards. The highest score in job satisfaction was related to the "nature of nursing work" domain with average score of 3.1 and the lowest score was related to the "salary and income" domain with average score of 2.5. Conclusion: The results of current study revealed a moderate level of job satisfaction in nurses. Pay has significant influence on job satisfaction that should not be ignored. It seems the right of nurses based on Health Sector Evolution Plan in Iran is critical in job satisfaction.